2011
DOI: 10.1159/000323324
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of NF-ĸB Signals in Heat Stress-Associated Increase in Protein Content of Cultured C2C12 Cells

Abstract: Heat stress is one of the hypertrophic stimuli on mammalian skeletal muscle. Nuclear factor-ĸB (NF-ĸB) signaling plays an important role in the regulation of skeletal muscle mass. However, the effects of heat stress on NF-ĸB signaling in skeletal muscle cells remain unclear. Effects of heat stress and/or administration of BAY11-7082, an inhibitor of NF-ĸB, on NF-ĸB signals and protein content of skeletal muscle were studied by using cell culture system. Differentiated mouse myoblasts (C2C12) were subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 90 publications
0
20
1
Order By: Relevance
“…Cell culture was performed as we described previously (11,33). Mouse myoblast C 2C12 cells were cultured on six-well culture plates with type I collagen-coated surface (Biocoat; BectonDeckinson Labware, Franklin Lakes, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell culture was performed as we described previously (11,33). Mouse myoblast C 2C12 cells were cultured on six-well culture plates with type I collagen-coated surface (Biocoat; BectonDeckinson Labware, Franklin Lakes, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Sample preparation was performed with some modification of the previously reported method (33). Briefly, the cells in each well were rinsed twice with 1 ml of ice-cold phosphatebuffered saline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of cytokine inhibition may be through activation of the heat shock response leading to inactivation of the NF-κB inflammatory pathway (Dokladny et al 2010;Paimela et al 2011). In this model, upregulation of heat shock factor-1 (HSF-1) and heat shock protein 70 or HSP70 (HSPA1A/B) (Kampinga et al 2009) prevented phosphorylation of nuclear factor of kappalight-polypeptide gene enhancer in B cells inhibitor, alpha (IκBα) leading to cytosolic housing of NF-κB (Dokladny et al 2010;Ohno et al 2011). We have previously demonstrated that 7 days of glutamine supplementation upregulated HSP70 and increased de-phosphorylated IκBα in PBMCs, along with preventing intestinal permeability in response to exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they strongly suggested that the NF-κB signaling pathway is directly involved in CXCL1 expression in response to EPS-evoked contractility [19] . However, NF-κB signaling was reported to be downregulated by hyperthermia in mouse myoblast cells [20] . These results of the above studies might explain the lack of change in serum CXCL1 level and the increase in serum IL-6 level after hot-HOI.…”
Section: Discussionmentioning
confidence: 99%